Evaluation of the Success Rate of Assisted Reproductive Techniques (ART) in Shahid Beheshti Infertility Center, Isfahan, Iran - Roshanak Abutorabi; Vida Razavi; Shekufeh Baghazadeh; Laleh Sharegh; Fatemeh Sadat Mostafavi (مجله دانشکده پزشکی اصفهان, 2014)
Background: Today, usage of assisted reproductive techniques (ART) has been resolved the problem of many infertile couples. Repeated treatment cycles, long time and high cost, problems due to repeated anesthesia, has been directed the researchers to find ways to predict the success rate of each method. This study aimed to evaluate the success of assisted reproductive techniques in Isfahan Shahid Beheshti infertility center, Iran.